(untitled) (Revista Espinhaço, 2021)
This paper presents the results of part of the efforts of the team at the UFVJM’s Laboratory of Archeology and Landscape Study to working closely with the communities of the Felício dos Santos, Minas Gerais state, Brazil. It’s a action beyond Extension or Extroversion, but in a collaborative way, we have understanding the communities as co-producers of knowledge. From this perspective, we have used the concept of Landscape to understand the experiences of communities in Felício dos Santos and their relationships with the archaeological record with which they live daily and they organize narratives about origins, meanings, cultural heritage and possibilities of life. We started the discussion with the presentation of the physiographic characteristics and the archaeological data obtained by the investigations, to then argue about the local narratives that involve this multiplicity of knowledge, both in materiality and in immateriality. e aim is to underline how many archaeological sets and landscape landmarks are present in communities’ lives in a very intrinsic way, from basic subsistence issues to reflections on the cosmos. Our attention was based on the cultural diversity of Jequitinhonha Valley and on the ethical and political-social engagement of the UFVJM. Finally, we conclude this text for the defense of the regional cultural heritage and of the communities which are responsible for the preservation of multiplicity of existences in the Alto Araçuaí Valley.